Uji Mutagenik Ames untuk Melengkapi Data Keamanan Ekstrak Gambir (Uncaria gambir Roxb.) - Sulistyaningrum, Novi; Alegantina, Sukmayati; Rustanti, Lina (Jurnal Kefarmasian Indonesia, 2013)
The main compound of Uncaria gambir Roxb. (gambir), catechin and it’s derivates have been believed to be potential as antiviral. Epigallocatechin gallate (EGCG) and epicatechin are catechin derivates which are found to be potential as antiviral against Human Immunodeficiency Virus (HIV). However, gambir extract also contains quercetin that has possibility to be mutagenic. Therefore, a preliminary study towards safety of those compounds within gambir extract, mutagenicity assay using Ames Method has been performed.Sample (gambir extract) was obtained from West Sumatera, Indonesia. The extract was characterized according to Farmakope Herbal Indonesia and WHO methods. Mutagenicity test by Ames method utilized a colorimetric microplate in 6 various concentration (125 mg/mL; 62.5 mg/mL; 31.25 mg/mL; 15.625 mg/mL; 7.81 mg/mL dan 3.91 mg/mL) against mutant bacteria Salmonella typhimurium TA 98, Salmonella typhimurium TA 100 and Escherichia coli WP2 uvrA with and without the addition of S-9 enzyme. Extract of gambir in this study contains 86.60% of catechin, 12.92% moisture content, 22.49% water-soluble extract content, 80.63% ethanol-soluble extract content, 0.81% total ash, 0.32% acid insoluble ash content and 10.38% in dryness level. From the mutagenicity test and calculation, fold increase (over baseline) of the sample in 6 various concentration with and without adding S-9 enzyme are lower than 2. Gambir extract from West Sumatra with catechin contains 86.6% hasn’t showed mutagenic effect due to the fold increase (over baseline) of mutagenicity test lower than 2.